CHARACTER CONTENT IN FICTION TEXT BOOK CLASS IV ELEMENTARY SCHOOL - Diah WIidyani, - (2022)
ABSTRACT This research is motivated by a moral crisis in Indonesian society because learning is carried out on the intellectual aspect as a measure of the success of building good character. This study aims to analyze the five main values of character education in fictional texts on learning materials for elementary school students in the perspective of the five main values of character education. The five main values of character education are religious, nationalist, independent, mutual cooperation, and integrity. The reason this research was conducted as a guide for teachers based on the content of the text to facilitate the implementation of character education through fictional texts in elementary schools. The method used in this research is content analysis and the object of this research is eleven fictional texts in the fourth grade elementary school student book 2013 curriculum published by the Ministry of Education and Culture in the 2017 revised edition. The results show that the five main values of character education are in eleven texts but not all character values main is contained in one text. The highest to least character values are mutual cooperation, independence, integrity, religious, and nationalism. The value of mutual cooperation is spread in twenty sentences in nine texts, independent value is spread in seventeen sentences in seven texts, the value of integrity is spread in sixteen sentences in seven texts, religious value is spread in four sentences in four texts, and nationalist spread in two sentences on two texts.